2022
DOI: 10.2174/1874467214666210525160944
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Post-traumatic Stress Disorder (PTSD): Symptoms, Therapies and Recent Case Studies

Abstract: : Post-traumatic stress disorder (PTSD), previously known as battle fatigue syndrome or shell shock, is a severe mental disturbance condition that is normally triggered by the experience of some frightening/scary events or trauma where a person undergoes some serious physical or mental harm or threatened. PTSD is a long-life effect of the continuous occurrence of traumatic conditions which, leading the production of feelings of helplessness, intense fear, and horror in the person. There are various examples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 90 publications
0
15
0
1
Order By: Relevance
“…Intentando ir mucho más allá de la descripción de los síntomas psicológicos, la evidencia y los metaanálisis señalan que, las personas con traumas severos derivados de la guerra o de contextos en donde persevera la violencia a menudo tienden a experimentan problemas de carácter interpersonal, lo que suele estar aunado a problemas típicamente psicosociales y de decaimiento en la calidad de vida y en la salud. Es justamente en los indicadores de calidad de vida en donde se encuentran mayores alteraciones, pues la guerra produce afectaciones en las personas, generando cuadros clínicos tan graves, que las incapacidades médicas se disparan al alza en las poblaciones afectadas o permeadas por la guerra (Sileo, Kershaw, Gilliam, Taylor, Kommajosula & Callands, 2021;Thakur, Choudhary, Kumar & Chaudhary, 2022).…”
Section: Resultados Y Discusiónunclassified
“…Intentando ir mucho más allá de la descripción de los síntomas psicológicos, la evidencia y los metaanálisis señalan que, las personas con traumas severos derivados de la guerra o de contextos en donde persevera la violencia a menudo tienden a experimentan problemas de carácter interpersonal, lo que suele estar aunado a problemas típicamente psicosociales y de decaimiento en la calidad de vida y en la salud. Es justamente en los indicadores de calidad de vida en donde se encuentran mayores alteraciones, pues la guerra produce afectaciones en las personas, generando cuadros clínicos tan graves, que las incapacidades médicas se disparan al alza en las poblaciones afectadas o permeadas por la guerra (Sileo, Kershaw, Gilliam, Taylor, Kommajosula & Callands, 2021;Thakur, Choudhary, Kumar & Chaudhary, 2022).…”
Section: Resultados Y Discusiónunclassified
“…Examining data from two population-based cross-sectional studies, Szepietowska et al found that pregnancy loss and risk for psychiatric disorders increased in their study (12). In addition, earlier pregnancy loss has been shown to negatively affect mood and psychological well-being, particularly in young women (13). In addition, they reported that depressive symptoms and depressive disorders were more common in women with a history of pregnancy loss (14).…”
Section: Discussionmentioning
confidence: 96%
“…Some examples of traumatic events are sexual assault, domestic violence, childhood abuse, serious injury, illness, transportation accidents, natural disasters, or any stressful events that threaten personal lives or those of their close ones [ 2 ]. The major symptoms of PTSD include flashbacks of traumatic events, sleep disturbance, nightmares, rumination, negative thoughts, avoidance, and dysregulated hyperarousal [ 3 ]. While exposure to trauma is common, only a minority will develop and meet the full diagnostic criteria of PTSD [ 4 ].…”
Section: Introductionmentioning
confidence: 99%